Delayed diagnosed trauma in severely injured patients despite guidelines-oriented emergency room treatment: there is still a risk - Höppchen, Arnold; Baran, Kristine; Brunnemer, Suna; Köck, Manuela Ursula; Obertacke, Udo; Eschmann, David (European journal of trauma and emergency surgery, 2022)
Emergency trauma room treatment follows established algorithms such as ATLS®. Nevertheless, there are injuries that are not immediately recognized here. The aim of this study was to evaluate the residual risk for manifesting life-threatening injuries despite strict adherence to trauma room guidelines, which is different to missed injuries that describe recognizable injuries.
Online veröffentlicht: 29. Juli 2021
Gesehen am 03.04.2023